The Influence Of Digital Marketing And Brand Image On The Competitiveness Of Micro, Small, And Medium Enterprises (Msmes) Among Generation Z At The Pondok Jawi Restaurant In Lahat - Putri Larasati; Marko Ilpiyanto; Titi Hasanah (Journal of Management, Economic, and Accounting, 2026)
The purpose of this study was to determine the influence of digital marketing and brand image in increasing the competitiveness of MSMEs among Generation Z at Pondok Jawi Restaurant, Lahat. The results showed that (1) digital marketing has a significant partial effect on competitiveness, as evidenced by the calculated t value > t table (7.250 > 1.989). (2) brand image has a significant partial effect on competitiveness, as evidenced by the calculated t value > t table (3.298 > 1.989). (3) digital marketing and brand image have a significant simultaneous effect on competitiveness, as evidenced by the calculated f value > f table (61.564 > 3.956), with a significance value lower than the significance level (a) of 0.05 (0.000 < 0.05).